Antioxidant Activity of Commercial Ready-to-Drink Orange Juice and Nectar - Stella, Suzana P. [UNESP]; Ferrarezi, Alessandra C. [UNESP]; dos Santos, Karina O.; Monteiro, Magali [UNESP] (Wiley-Blackwell, 2011)
Total antioxidant activity (TAA), total phenolic compounds (TPC), and physicochemical characteristics of ready-to-drink orange juice and nectar from the most consumed brands available in Brazil were evaluated. TPC ranged from 18.7 to 54.2 mg of gallic acid/100 mL, and TAA varied from 57.88 to 349.32 mu mol TEAC/100 mL ready-to-drink orange juice and nectar. The ascorbic acid content was the only physicochemical parameter that showed strong variation among packages and brands. Correlation of TPC with TAA showed that the higher the level of TPC the higher the TAA. Correlation of ascorbic acid content with TAA is higher for ready-to-drink orange juice than nectar. The same was found for the correlation of ascorbic acid content with TPC. The results confirm the contribution of the TPC to TAA.
Keywords: ABTS; antioxidant activity; ascorbic acid; orange juice; ready-to-drink orange juice and nectar; total phenolic compounds